CUSTOMER AND SHAREHOLDER SATISFACTION IN THE INSURANCE INDUSTRY - Ahmad Reza Assary , Milad Einali , Shirin Eskandari , Nasim Hamrahi , Morteza Javid Anbardan , Mohsen Johari Miyab (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The number of companies that choose customer satisfaction as an indicator of the performance of their product or service is constantly increasing. The main issue of research is customer and shareholder satisfaction in the insurance industry. After reviewing previous studies and a survey of insurance industry experts, the model used was selected as the initial model and the group postal model was proposed as a conceptual model of the research. The statistical population of this study is the insured victims of insurance companies throughout Iran and also the visual language (in the field of liability and third party insurance) which through the insured, in the period from 2012 to 2014, received damages from the insurance company. The results show that the level of customer satisfaction with insurance companies in the compensation stage is lower than the level of satisfaction in the issuance stage and in general, customer satisfaction with compensation and grievance redress is low. In contrast, the level of customer satisfaction in categories such as simplicity and speed of issuance, responsiveness, staff trap and physical environment is relatively higher compared to other satisfaction variables.